Cooperative Development: Sustainability Agricultural Planning Viewed Through Cooperative Equilibrium Management Theory in Togo, Africa - Berge, Simon T.; Bokoumbo, Koudima; Johnson, Kuawo Assan; Yabi, Jacob Afouda; Yegbemey, Rosaine Nerice (Frontiers in Sustainable Food Systems, 2021)
Cooperative economics looks at market failures as areas for development. The cooperative development process, however, requires member engagement or cohesion in the process according to the Cooperative Management Equilibrium Theory. This cohesion requires an awareness and understanding by the cooperative members of the market failure to develop the capacity to address the failure. This article looks at the effects of government agricultural programs on economic, environmental and social sustainability. The questions we ask is how does a focus on economic development push against social and environmental sustainability within the agricultural sector in Togo? Does member cohesion within a cooperative represent a form of Polanyian double movement through social and environmental cohesion? The current development models utilize what Sen refers to as an austere mode of development which forgoes social or environmental considering them luxuries. Does the focus of economic development build capacity only for economic performance within the Togo agricultural sector at the expense of social and environmental sustainability? Utilizing Deep Participatory Indicator Approach (DPIB) approach this paper examines the economic, environmental and social indicators within two prefectures in the Plateaux Region of Togo. Indicators were separated to show the differences between individual or cooperative producers. As cooperatives it was anticipated that a greater emphasis on social and environmental sustainability would be created through cohesive social action. This study found that the emphasis on economic development included in government programs built development capacity within cooperatives emphasizing their cooperative market cohesion.